Hubungan Konsumsi Makanan Berlemak, Aktivitas Fisik, dan Kelebihan Berat Badan dengan Hipertensi pada Wanita Usia Subur di Bintang Metropol Bekasi - Hafni, Ranayah Putri; Faridi, Ahmad (HB PRESS, 2024)
Hypertension is also called “the silent killer” because this disease has no complaints in sufferers, so many hypertension sufferers do not know that they have hypertension and only find out after complications occur. The aim of this study was to analyze teh relationship between consumption of fatty foods, physical activity, and being overweight and hypertension in women of childbearing age in Bintang Metropol Bekasi. This research uses a cross sectional study design. Descriptive quantitative approach. Data collection by observation, measurement and interviews. The data analysis used was univariate analysis and bivariate analysis with Chi-Square and Fisher Exact tests. Based on the results of univariate analysis, data showed that 50,8% of respondents had hypertension, 2% of respondents had excessive consumption of fatty foods, 51% of respondents had light physical activity, 53% of respondents were overweight. The results of bivariate analysis showed that there was no significant relationship between consumption of fatty foods and hypertension in women of childbearing age (p value =0,240 > 0,05). However, there is a significant relationship between physical activity and overweight and hypertension in women of childbearing age (p value = 0,045 < 0,05) and overweight and hypertension in women of childbearing age at Bintang Metropol Bekasi (p value = 0,000 < 0,05). The suggestions from this research, for The community is aimed at increasing knowledge and awareness of health, especially for people who have blood pressure above the normal category and excessive consumption of fatty foods.